2019
DOI: 10.1021/acs.energyfuels.9b02104
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into Anaerobic Digestion of Rice Straw Using Combined Pretreatment with CaO and the Liquid Fraction of Digestate: Anaerobic Digestion Performance and Kinetic Analysis

Abstract: Combined pretreatment using CaO and the liquid fraction of digestate (LFD) was proposed as an eco-friendly pretreatment method for high-quality anaerobic digestion (AD). In this study, rice straw was pretreated by CaO–LFD at three pretreatment temperatures (5, 20, and 35 °C) and four pretreatment times (1, 2, 3, and 4 days). The results showed that the optimum pretreatment condition for rice straw was 35 °C for 2 days. In this case, the maximum biomethane yield reached 308 mL g–1 of VS, 77.4% higher than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Alternatively, it was obviously observed that the CH 4 production of T0 (372 ± 24 mL/gVS) was even higher than that of MBL (331 ± 33 mL/gVS). It would probably indicate that all of the reactors were started with the mesophilic inoculum taken from a mesophilic AD plant, without prior thermophilic acclimation for M0, MBL, MBS, and MAB, which limited the abundance of thermophiles . Simultaneously, it also indicated that 2 cm biochar and <5 μm biochar addition was insufficient to overcome the temperature shock from mesophilic to thermophilic on the reactors that inoculated the mesophilic inoculum during the inhibited steady state.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it was obviously observed that the CH 4 production of T0 (372 ± 24 mL/gVS) was even higher than that of MBL (331 ± 33 mL/gVS). It would probably indicate that all of the reactors were started with the mesophilic inoculum taken from a mesophilic AD plant, without prior thermophilic acclimation for M0, MBL, MBS, and MAB, which limited the abundance of thermophiles . Simultaneously, it also indicated that 2 cm biochar and <5 μm biochar addition was insufficient to overcome the temperature shock from mesophilic to thermophilic on the reactors that inoculated the mesophilic inoculum during the inhibited steady state.…”
Section: Resultsmentioning
confidence: 99%
“…First, our experimental inoculum seed was acclimated with mesophilic anaerobic sludge, which limited the abundance of thermophiles. 24 Second, 59 °C was the key to the reconstruction of methanogenic from thermophilic to hyperthermophilic temperatures, potentially leading to prolonged reconstruction to hyperthermophilic temperatures. Overall, our results indicate that a mesophilic reactor would be able to maintain stability (or high performance at 32−41 °C) at a temperature below the 47 °C threshold, with no obvious process perturbation induced by changing from mesophilic to thermophilic temperatures.…”
Section: ■ Resultsmentioning
confidence: 99%
“…At 59 °C, this can be explained by two phenomena. First, our experimental inoculum seed was acclimated with mesophilic anaerobic sludge, which limited the abundance of thermophiles . Second, 59 °C was the key to the reconstruction of methanogenic from thermophilic to hyperthermophilic temperatures, potentially leading to prolonged reconstruction to hyperthermophilic temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Received: January 6, 2020 Published: January 31, 2020 4 Novel Insights into Anaerobic Digestion of Rice Straw Using Combined Pretreatment with CaO and the Liquid Fraction of Digestate: Anaerobic Digestion Performance and Kinetic Analysis Zhao 5 Catalytic Pyrolysis of Herb Residues for the Preparation of Hydrogen-Rich Gas de Caprariis 6 Biomass Gasification: The Effect of the Surface Area of Different Materials on Tar Abatement Efficiency Chen 7 Hydrothermal Liquefaction of Sewage Sludge by Microwave Pretreatment Tao 8 Hydrogen Production via Aqueous-Phase Reforming of Ethylene Glycol over a Nickel−Iron Alloy Catalyst: Effect of Cobalt Addition Andrews 9 Anode-Boosted Electrolysis in Electrochemical Upgrading of Bio-oils and in the Production of H 2 Jin 10 Study on the Solubility between Diesel and Acetone− Butanol−Ethanol with or without Water Liu 11 Ammonia Measurements with Femtosecond Two-Photon Laser-Induced Fluorescence in Premixed NH 3 /Air Flames Ren 12 Modeling Study of the Impact of Blending N…”
Section: Complete Contact Information Is Available Atmentioning
confidence: 99%
“…Three of the papers deal with synergies between industries that benefit the production of renewable fuels. The next entries in the table exemplify depolymerization processes that convert the renewable feedstock into more valuable streams, including cleaner water .…”
mentioning
confidence: 99%